Detection of Hepatitis Antibodies using ELISA Technique in Basrah Province - Fayad, Ahmed Naser (University of Thi-Qar Journal of Science, 2013)
The possibility of detecting acute infection and immunity using body fluids those are easier to collect than blood, mainly in children, would facilitate the investigation and follow-up of outbreaks of hepatitis A (HAV). So to evaluate the detection of anti-HAV type IgM, IgA and total antibodies in saliva using serum samples as reference. Forty three paired serum and saliva samples were analyzed. From this total, 24 samples were obtained from children and 1 from one adult during the course of acute hepatitis A; an additional 18 samples were obtained from health professionals from Basrah hospital. The sensitivity to detect anti-HAV IgM was 100% (95%CI: 79.1 to 100.0%), employing saliva as clinical samples. In detecting anti-HAV IgA, the sensitivity was 80.8% (95%CI: 60.0 to 92.7%) and for the total antibodies was 82.1% (95%CI: 62.4 to 93.2%). The specificity was 100% for each. The rate of agreement was high comparing the results of serum and saliva samples for detecting HAV antibodies. We conclude that saliva is an acceptable alternative specimen for diagnosing acute hepatitis A infection, and for screening individuals to receive hepatitis A vaccine or immunoglobulin.